2023
DOI: 10.1108/jaar-10-2022-0279
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability disclosures and corporate boards: a stakeholder approach to decision-making

Abstract: PurposeThe board of directors of an organization can contribute considerably to the transition to a sustainable global economy by accommodating environmental, social and governance (ESG) measures in the directors' business model. Along these lines, the purpose of this research is to understand the nexus between the board's structural attributes and sustainability disclosures in an emerging economy such as India.Design/methodology/approachThe authors investigate this link using the system generalized method of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 62 publications
1
7
0
Order By: Relevance
“…When it comes to contribution by geographical location, the analysis shows that Europe had the highest number of publications (1150), followed by Asia (885), North America (495) and Oceania (142). This reinforces a similar finding by [34] and emphasizes the leading role of these continents in this area of research and further to the fact that research related to CSR and business performance is growing in popularity in these areas.…”
Section: Most Productive Geographic Locationssupporting
confidence: 69%
See 2 more Smart Citations
“…When it comes to contribution by geographical location, the analysis shows that Europe had the highest number of publications (1150), followed by Asia (885), North America (495) and Oceania (142). This reinforces a similar finding by [34] and emphasizes the leading role of these continents in this area of research and further to the fact that research related to CSR and business performance is growing in popularity in these areas.…”
Section: Most Productive Geographic Locationssupporting
confidence: 69%
“…In [140], the nexuses between CSR adoption, business strategies and governance were explored. The study by [141] investigated the relationship between corporate environmental performance (CEP) and innovation, and finally, [142] studied the connection between board structural attributes and sustainability disclosure in the context of an emerging economy.…”
Section: Gaps and New Research Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The short-term effects of ESG score on market value can be studied using the CL effects system dynamics model, which allows for the analysis of complex systems with feedback loops [51,52]. Several recent studies have used this approach to explore the dynamics of the relationship between market value and ESG score [41,49,[53][54][55][56][57][58][59]. For instance, a study by [53] found that an increase in a firm's ESG score leads to an increase in its market value, which in turn leads to an increase in the firm's ESG score.…”
Section: Short-term System Dynamicsmentioning
confidence: 99%
“…The long-run relationship between ESG scores and market value is not limited to positive effects alone. A study by [40,53] found that firms with high ESG scores may also face higher agency costs, which can negatively impact their value in the long run. The authors used a system dynamics approach to model the complex relationships between ESG scores, agency costs, and market value and found that the negative impact of agency costs can offset the positive effects of ESG scores on market value.…”
Section: Long-term System Dynamics Effectsmentioning
confidence: 99%